Limited Access to Education for Out-of-School Children in Pakistan: Exploring Barriers and Suggesting Measures - Khalid, Iram (Annals of Human and Social Sciences, 2023)
Human resource development stimulates sustainable economic growth of a country. In Pakistan, 16 percent of children aged 5-16 not attending school. The out-of-school children, due to socio-economic and cultural reasons, are deprived of their fundamental right to education and face bleak economic and social prospects. To uncover the varying perspectives of the educational experts, schools, parents and children, semi-structured interviews and surveys will be conducted. The use of technology, model of schooling, parental behavior, smart schooling amongst others drive the high dropout rate in public schools and discourage others from enrolling. Through quantifying the key underlying reasons obstructing access to education, this study aims to capture the local nuances and facilitate the policy makers to design the policy framework with efficient allocation of resources, in order to improve enrollment rates of out-of-school children.